Pengaruh Model Pembelajaran Group Investigation Terhadap Peningkatan Aktivitas Belajar Fiqih Siswa Kelas VIII MTs Al-Hidayah Sei Tualang - Ahmad Sanusi Luqman, Muamar Al Qadri, Bagus Tiansyah (Pusdikra Publishing, 2022)
The background of this research is that based on the identification carried out by the researchers at the research location, namely: The learning that has been carried out so far at MTs Al Hidayah Sei Tualang specifically for Fiqh subjects does not emphasize learning by providing direct learning experiences through the development of process skills, scientific attitudes and lack of developing thinking skills. This causes the low ability of student learning activities. The objectives of this research are: To determine the effect of the application of the Group Investigation learning model on the learning activities of fiqh students of class VIII MTs Al-Hidayah Sei Tualang. The type of research used in this study is a quantitative research method. In this study the form of the instrument used is a questionnaire using a Likert scale attitude which has been modified with the following assessments: Often a score of 3, Sometimes a score of 2, and never a score of 1. The results of this study are: There is a moderate influence /enough between the Group Investigation Learning Model on the Improvement of Students' Learning Activities in Class VIII Fiqh learning at MTs Al Hidayah Sei Tualang, which is 0.413.